2020
DOI: 10.1094/phyto-09-19-0351-r
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Level Identification of Bacterial Tomato Pathogens Directly from Metagenomic Sequences

Abstract: Routine strain-level identification of plant pathogens directly from symptomatic tissue could significantly improve plant disease control and prevention. Here we tested the Oxford Nanopore Technologies (ONT) MinION sequencer for metagenomic sequencing of tomato plants either artificially inoculated with a known strain of the bacterial speck pathogen Pseudomonas syringae pv. tomato or collected in the field and showing bacterial spot symptoms caused by one of four Xanthomonas species. After species-level identi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Because this approach can be directly used on plant extracts, it is not biased toward known sequences and provides more information about the pathogen genome, such as virulence traits. Metagenomics, the study of genetic material from environmental samples, beyond whole-genome sequencing, allows for the detection of strains from several subspecies and ST at the same time from the host ( 20 ). Recently, the use of long-read sequencing as diagnostic tool identified Xf subspecies and ST from infected samples ( 12 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because this approach can be directly used on plant extracts, it is not biased toward known sequences and provides more information about the pathogen genome, such as virulence traits. Metagenomics, the study of genetic material from environmental samples, beyond whole-genome sequencing, allows for the detection of strains from several subspecies and ST at the same time from the host ( 20 ). Recently, the use of long-read sequencing as diagnostic tool identified Xf subspecies and ST from infected samples ( 12 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to results using metagenomic sequencing for the identification of bacterial plant pathogens, the recovery of fungal pathogen reads in this study was relatively low. In fact, up to 60% of reads were identified as the bacterial pathogen Xanthomonas perforans in tomato plants naturally infected with bacterial spot 23 . However, for fungal plant pathogens, other studies reported recovery of very few pathogen reads.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to plant disease diagnostics, metagenomic sequencing with the MinION using DNA or RNA extracted directly from plants enables rapid pathogen detection and identification in almost any laboratory or even in the field 20 . However, so far, the MinION has mainly been used to identify plant pathogenic viruses 21 , 22 and bacteria 23 , 24 . Few studies have reported using the MinION for detection of plant pathogenic fungi 19 , 25 , which is challenging because of the poor representation of fungal genomes in reference databases and the technical difficulties in isolating high quality fungal DNA directly from plant tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the combination of ONT and Illumina technologies can be used to improve the quality of sequence assembly in metagenomic studies [ 93 ]. Metagenomic sequencing with MinION TM has already been used to identify fungal, bacterial, and viral pathogens on tomato and several other crops [ 94 , 95 , 96 ], and the current trend towards lower sequencing costs while improving quality suggests that direct sequencing is likely to be the next step in metagenomics [ 97 ].…”
Section: Genomicsmentioning
confidence: 99%